The max-out min-in problem - Cerdeira, Jorge Orestes (2023)
Funding Information: The first and third authors were financially supported by the Fundação para a Ciência e a Tecnologia, Portugal (Portuguese Foundation for Science and Technology) through the projects UIDB/MAT/00297/2020 , UIDP/MAT/00297/2020 (Centro de Matemática e Aplicações). Publisher Copyright: © 2023 The Author(s)